Leadership practices, universal work values and National Key Results : a study on Malaysian education system - Rosninah binti Ghani (Kulliyyah of Education, International Islamic University Malaysia, 2018)
This study investigates the relationship between leadership practices, followership practices, strategic leadership practices and universal work values of the Malaysian educational leaders towards the National Key Result Areas achievements. A cross-sectional survey was conducted among Ministry of Education leaders. A total of 1068 respondents which were selected through stratified random sampling participated in this survey. The questionnaire consists of five constructs namely Leadership Practices Instrument (LPI) and Followership Practices Instrument (FPI) adapted from Ministry of Education Leaders, Strategic Leadership Practices (SLP) adopted from Davies Strategic Leadership Style, Universal Work Value (UWV) adapted from Islamic Work Ethic and a self-developed construct on leader's target of NKRAs achievement. Data were analysed descriptively using SPSS software while the research model were tested using the Partial Least Squares Structural Equation Modelling (PLS-SEM) analysis aided in SmartPLS 3 software. The findings shows that the Malaysian educational leaders Leadership Practices and Strategic Leadership Practices have a significant influence on NKRAs achievement. The Leadership Practices, Followership Practices and Strategic Leadership Practices also shows the significant influence on Universal Work Value. A mediating effect test shows that Universal Work Value partially mediate the relationship between Leadership Practices and the NKRAs achievement. Thus, this result suggest that the leadership practices, followership practices and strategic leadership practices is practical to be built from exemplary education leaders. The indicators of these constructs should be used as evaluation instruments during the selection and evaluation process of new exemplary education leader. A universal work value is important work culture to leap the leadership practices towards NKRAs achievement.